Strengthening Digital Citizens Against Love Scams: A Case Study of Indonesia and Thailand - Sasiwimon Temcharoenkit; Antika Dwi May Rani (Jurnal Pendidikan Sosial Indonesia, 2025)
The phenomenon of love scams has rapidly expanded in Southeast Asia, particularly in Thailand and Indonesia, producing significant financial, psychological, and social impacts. The high exposure rates in Thailand and the increasing reports in Indonesia highlight that digital citizens’ vulnerabilities stem not only from technical limitations but also from emotional factors, cultural norms, and weak regulations. This study aims to analyze the development of love scams in both countries and to identify the role of social education in strengthening digital literacy. Adopting a qualitative approach with a comparative case study design, the research relied on secondary data, including official reports, academic publications, and media coverage. Thematic analysis was applied to identify patterns, vulnerabilities, and preventive strategies. Findings reveal that Thailand emphasizes technological and legal reinforcements, while Indonesia focuses more on public education, though both face distinct challenges. The study concludes that integrating social education and digital literacy is essential for effective prevention and calls for cross-national collaboration and provision of psychosocial support for victims. Its key contribution lies in extending the discourse on love scams into the field of social education, ensuring that the issue is not confined solely to legal or technological domains.